2006
DOI: 10.1182/blood-2005-06-2552
|View full text |Cite
|
Sign up to set email alerts
|

Circulating thrombopoietin as an in vivo growth factor for blast cells in acute myeloid leukemia

Abstract: Thrombopoietin (TPO), the major growth factor for cells of the megakaryocytic lineage, is removed from circulation by binding to c-mpl receptors present on platelets and megakaryocytes. We studied patients with acute lymphoblastic leukemia (ALL) or acute myeloblastic leukemia (AML) and used TPO-induced c-fos protein up-regulation as a marker of cmpl functionality and observed that cmpl-presenting blast cells were present in 62% (37 of 60) of patients with ALL but that c-mpl was nonfunctional in 0 of 28 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 33 publications
1
24
0
3
Order By: Relevance
“…Given the models of TPO homeostasis described previously, severe thrombocytopenia should result in increased circulating TPO. However, consistent with prior studies, 6 The biology of TPO and MPL is complex, and TPO and its receptor MPL play pleiotropic and far more important roles in regulating hematopoiesis than simply triggering thrombopoiesis. TPO can both induce expansion of HSCs but also paradoxically maintain HSC quiescence, possibly by operating at different signaling levels.…”
Section: Goldberg and Martin S Tallman Memorial Sloan Kettering Cancsupporting
confidence: 80%
See 2 more Smart Citations
“…Given the models of TPO homeostasis described previously, severe thrombocytopenia should result in increased circulating TPO. However, consistent with prior studies, 6 The biology of TPO and MPL is complex, and TPO and its receptor MPL play pleiotropic and far more important roles in regulating hematopoiesis than simply triggering thrombopoiesis. TPO can both induce expansion of HSCs but also paradoxically maintain HSC quiescence, possibly by operating at different signaling levels.…”
Section: Goldberg and Martin S Tallman Memorial Sloan Kettering Cancsupporting
confidence: 80%
“…As an alternative, blast eradication with induction chemotherapy serves as an effective method for increasing TPO levels in AML patients with MPL-expressing blasts. 6 Although it is unlikely that TPO scavenging by MPL is the only determinant of cytopenias in AML patients, the work by Rauch et al supports an intriguing and novel model to explain the impairment of normal hematopoiesis in patients with AML. By stealing TPO, high levels of MPL on AML blasts might leave AML patients down for the count.…”
Section: Goldberg and Martin S Tallman Memorial Sloan Kettering Cancmentioning
confidence: 98%
See 1 more Smart Citation
“…20,44 It is well known that c-Mpl is expressed not only by hematopoietic progenitors, but also by many malignant hematopoietic cell types, and different in vitro experiments demonstrated that thrombopoietin may sustain the growth of both leukemic cell lines and human leukemic cells. 45,46 The concern that thrombopoietin mimetics might favor leukemogenesis has been extensively debated. A rise in blast counts has been seen in patients with MDS receiving romiplostim, 47 and a recent retrospective study of a large series of ITP patients indicated an association between the administration of thrombopoietin mimetics and the development of AML.…”
mentioning
confidence: 99%
“…2,8,9 One of these, a nonpeptidyl, hydrazone class small molecule, named Eltrombopag (E; SB-497115), was recently approved by the Food and Drug Administration for use in adult chronic idiopathic thrombocytopenic purpura patients. 10,11 Because Mpl and/or Tpo is expressed by many malignant hematopoietic cell types, [12][13][14] concern that Mpl agonists might exacerbate a leukemia patient's disease is appropriate. We investigated this issue using primary human leukemia cells and a prototype nonpeptidyl, hydrazone class, Mpl agonist, SB-559457 (SB; Figure 1A) whose in vitro megakaryocytopoietic properties are virtually indistinguishable from rhTpo (5M SB ϭ 100 ng/mL; 2.8M rhTpo).…”
Section: Introductionmentioning
confidence: 99%